Ebstein's anomaly during pregnancy: experience from a tertiary care centre – a case series and review of literature. (19th May 2022) - Suriya, J. Yavana; Raj, Ashwini; Pillai, Ajith Ananthakrishna; Satheesh, Santhosh; Plakkal, Nishad; Kundra, Pankaj; Keepanasseril, Anish
Abstract: Pregnancy complicated with uncorrected Ebstein's anomaly is uncommon and may pose a serious threat to maternal and foetal life in the clinical setting of altered hemodynamics of pregnancy. Data of eight pregnancies in four women with Ebstein's anomaly who delivered in a tertiary care institute was analysed. Among the four women, one had associated atrial septal defect, one had pulmonary hypertension and three had right bundle branch block. There were two miscarriages and six successful pregnancies resulting in live births. Three of the pregnancies were delivered by caesarean section. There was one pregnancy complicated by severe preeclampsia, no preterm births or maternal cardiac complications. There was one neonate with congenital ostium secundum atrial septal defect. All patients were managed by a multidisciplinary team involving Obstetrician, Cardiologist, Anaesthesiologist and Neonatologist. IMPACT STATEMENT: What is already known on this subject? Ebstein's anomaly is a rare congenital anomaly with apical displacement of the septal tricuspid leaflet in association with leaflet dysplasia. It may cause varied presentation in pregnancy depending on the severity of the lesion. What do the results of this study add? Ebstein's anomaly may become symptomatic for the first-time during pregnancy. Patients with NYHA class II symptoms and no cyanosis generally tolerate pregnancy well. Miscarriages and intrauterine growth restriction may occur in the presence of this condition. Vaginal delivery is advised and caesarean is done only for obstetric indications. What are the implications of these findings for clinical practise and/or future research? The management of pregnancy with uncorrected Ebstein's anomaly is highly challenging especially in a low resource setting and requires tertiary centre care. Multidisciplinary team involvement can help to improve the outcomes in such pregnancies.